Growth Performance of Local Chicken Breeds, a High-Performance Genotype and Their Crosses Fed with Regional Faba Beans to Replace Soy - Tanja Nolte; Simon Jansen; Steffen Weigend; Daniel Moerlein; Ingrid Halle; Wolfgang Link; Jürgen Hummel; Henner Simianer; Ahmad Reza Sharifi (Animals, 2020)
The faba bean (Vicia faba L.) is a native protein crop and considered a promising alternative to soybeans. Due to its anti-nutritive substances such as vicin and convicin (VC) its use in animal nutrition has been restricted. In the present study, two consecutive experiments were conducted to analyse the effects of feeding 20% faba beans, which differ in their VC content on fattening performance and slaughter traits of different chicken genotypes. In a first trial, purebred male chickens of the local breeds Bresse Gauloise and Vorwerkhuhn as well as of a high-performance White Rock line were tested. In a second trial, crossbreds of them were evaluated: Vorwerkhuhn x Bresse Gauloise, Vorwerkhuhn x White Rock, Bresse Gauloise x White Rock. Daily weight gain and feed intake were recorded until slaughter at approximately 2100 g. At slaughter the final live weight, carcass yield and the weights of the valuable parts (breasts and legs) were measured. For the genotypes studied, no adverse or undesirable effects of both VC−rich and VC−poor faba beans in the feedstuff were detected regarding body weight development, carcass quality, and fattening parameters. Furthermore, there was no indication that the birds’ health was impaired.